The 12th Conference of the International Sports Engineering Association 2018
DOI: 10.3390/proceedings2060311
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Landing in Ski Jumping by Means of Inertial Sensors and Force Insoles

Abstract: Landing and its preparation are important phases for performance and safety of ski jumpers. A correct ski positioning could influence the jump length as also the cushioning effect of the aerodynamic forces that permits the reduction of landing impacts. Consequently, the detection of ski angles during landing preparation could allow for analyzing landing techniques that result in reduced impact forces for the athletes. In this study, two athletes performed with force insoles and inertial sensors positioned on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…The outcomes of the force insoles during the entire performance (Figure 2) were comparable with those in previous publications [1,21,35]. The normal GRF max and the impulse were correlated with t flight (Table 1).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The outcomes of the force insoles during the entire performance (Figure 2) were comparable with those in previous publications [1,21,35]. The normal GRF max and the impulse were correlated with t flight (Table 1).…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the limitations of the studies, as previously mentioned, the low sample rate of the force insoles could have influenced the collected outcomes [35]. Therefore, during further studies, a higher sampling rate (200 Hz) of the loadsol insoles would be recommendable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature there is information on yaw (~ 15°-20°) and AoA angles (~ 25°-40°) used by ski jumpers during most of the flight phase (e.g., [4]), but less about roll of the ski around its longitudinal axis which corresponds to the edge angle described in the present study. Bessone et al [5] used inertial sensors to measure the edge angle of both skis during the flight phase of two jumpers. The angle ranged from 0° (flat ski) at the release instant from the take-off table to 30°-40° at mid-flight.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a combination of IMUs placed on the skis and wireless force insoles could represent an interesting set-up for this analysis. This combination has been previously introduced by the authors of the present paper, and the first results showed that the ski position influences the vertical ground reaction force (GRF) [24]. The combination of IMUs and force insoles proposed in [24] was utilized in the present study on a higher number of ski jumpers to detect possible correlation between ski position and impact kinetics.…”
Section: Introductionmentioning
confidence: 99%